Romanism of Latin American Jurists: Dalmacio Vélez Sarsfield - Louzan de Solimano, Nelly Dora (1986)
This article examines the influence of Romanism in the legal education of Latin American jurists, with emphasis on Dalmacio Vélez Sarfield, one of the three great referents along with Teixeira de Freitas and Andrés Bello. These jurists cemented the socio-political identity of Latin America, using Roman law as the basis of their legal systems. In particular, it analizes the impact of the Corpus Iuris and the Institutes of Justinian on legal education in universities such as Cordoba, which shaped Vélez Sarfield. His greatest legacy, the Argentine Civil Code, is highlighted as a legal work that merged the classical principles of Roman law with the contemporary needs of his country, guaranteeing legal certainty. The article also highlights the relevance of Roman law not only in legislation, but also in cultural and educational life, and how its influence continues despite regulatory changes, reaffirming its centrality in the Latin American legal tradition.